Peran Teknologi Informasi dalam Meningkatkan Transparansi dan Keterbukaan Pelayanan Publik: Perspektif Undang-Undang No. 25 Tahun 2009 - Maulana Ibrahim, Bartolomeus Marulitua Simanjorang, Bayu Ardian Syahputra, Lisa Caroline Pakpahan, R (Mediation : Journal of Law, 2023)
Law no. 25 of 2009 concerning Public Services provides the legal basis for improving the quality of public services in Indonesia. One of the key aspects of this law is transparency and openness of public services to support participation in community decision making. In the digital era, information technology plays an important role in supporting the implementation of these aspects. This research aims to investigate the role of information technology in increasing transparency and openness of public services, with a focus on the implementation of Law no. 25 of 2009. The aim is to ensure that implementation is in accordance with the principles of transparency and openness as regulated in Law no. 25 of 2009 concerning Public Services. The findings of this research indicate that the application of information technology in public services can effectively increase transparency and openness. Electronic information systems, public service portals and other dare platforms can provide easier access for the public to obtain information related to public services. Apart from that, information technology can also increase accountability and efficiency in the delivery of public services.